Innovation capability maturity in non-R&D performers: a reference model - Baptista Narcizo, Ramon; Gabbay Canen, Alberto; Tammela, Iara; Cardoso, Rodolfo; Eleutério Delesposte, Jamile (Brazilian Journal of Operations & Production Management, 2019)
Highlights: The prevalence of Research and Development (R&D) as an inducing factor for innovation has been questioned, and studies show that low-tech companies are able to innovate. Innovation capability is essential to increase productivity and improve competitiveness. However, when formal R&D is considered as the main parameter in its evaluation, it tends to underestimate it. The extent and heterogeneity of studies on innovation in non-R&D practitioners is a relevant problem and, despite theoretical and empirical advances, it is not satisfactorily resolved yet. Goal: This article presents a reference model for innovation capability maturity in low-technology, non-R&D performing companies, oriented to guide decision makers and the institutions supporting these organizations. Design / Methodology / Approach: The method used to construct the model is based on the proposition of Ahlemann and Gastl (2007) for the construction of reference models based on empirical evidence. Results: The model is based on ten organizational dimensions and their effects on the organization’s performance. Five maturity levels are defined, synthesizing the fundamental characteristics of innovation capability in non-R&D practitioners or low technology companies. Limitations of the investigation: Although the model has been tested and validated, more applications and tests may still be required. Practical implications: The model is an important tool for decision-making, at the management level, in low-tech companies that aspire to broaden their innovation capability. Originality / Value: The model has significant potential academic repercussions, in terms of the expansion of knowledge, as well as for the industry, since it can contribute to the increase of the competitive performance of companies.